Development of individual fitness score for conformity of prescriptions to the "Guidelines For Pharmacological Therapy of Schizophrenia". Issue 4 (18th October 2022) - Inada, Ken; Fukumoto, Kentaro; Hasegawa, Naomi; Yasuda, Yuka; Yamada, Hisashi; Hori, Hikaru; Ichihashi, Kayo; Iida, Hitoshi; Ohi, Kazutaka; Muraoka, Hiroyuki; Kodaka, Fumitoshi; Ide, Kenta; et al.
Abstract: Aims: The Guidelines for the Pharmacotherapy of Schizophrenia were established to improve the quality of medical care, and the EGUIDE project was conducted to train clinicians on guideline usage. A quality indicator (QI) was established to measure the prevalence of the guidelines, and a survey was conducted, which revealed a gap between the guidelines and actual clinical practice (evidence‐practice‐gap). The purpose of this study was to develop an individual fitness score (IFS) formula that expresses the degree to which prescribers adhere to the Guidelines for Pharmacological Therapy of Schizophrenia in a simple manner, and to determine the validity of this formula from a survey of the prescriptions of the EGUIDE project participants'. Methods: To establish appropriate scores, members discussed the proposed formula and then voted on them. The IFS formula developed was set up so that antipsychotic monotherapy would be given 100 points, with points deducted if concomitant or adjunctive antipsychotic medications were used, and a minimum score of 0. To validate this formula, prescriptions of hospitalized schizophrenic patients at admission and at discharge were scored and compared. Result: IFS points vary and ranged from 0 to100. The average pre‐admission score for all subjects was 45.6, and the average score at discharge was 54, those were significantly higher during discharge. Conclusions: We developed an IFS formula, a tool to easily visualize the degree to which current prescriptions conform to the guidelines for the pharmacological treatment of schizophrenia.